G, G ̅ Properties – from G ̅, G - Elakkiya, A.; Yamuna, M. (International Journal of Engineering and Technology, 2018)
In this paper weprovide a method of determining the chromatic polynomial of  without actual construction of . A planar graph characterization of graphs whose domatic partition is  using  properties is established and provide a MATLAB program for identifying just excellent graphs.